Identificationof the PhotoreactiveSpeciesof ProtonatedN‑Nitrosopiperidinein Acid Medium:A CASPT2and DFT Study - Soto-Martín, Juan (ACS, 2023)
In this work, we have studied the initial reaction step after photoexcitation of protonated N-nitrosopiperidine both in the gas and condensed phases. To achieve this end, we have applied the CASPT2 and MP2 wave function methods and the density functional theory approach. It is found that the site of protonation of N-nitrosopiperidine in acid medium depends on the solvent: protonation occurs at the oxygen atom in protic solvents, while in aprotic solvents, the proton is bonded at the N-atom of the amine moiety. Furthermore, protonation at such an N-atom is the unique protonated species that absorbs in the visible range and directly dissociates into aminium radical cation and nitric oxide.
Keywords: Química física; Absorption; Dissociation; Molecular structure; Reaction mechanisms; Solvents